Pengaruh Country Of Origin Dan Brand Image Terhadap Minat Beli Smartphone Asus Di Kota Semarang - Pradipta, Alvidy Brilian; Ngatno, Ngatno (Jurnal Ilmu Administrasi Bisnis, 2021)
Abstract: Globalization and technology advances is becoming a center of attention of local and international community of marketers develop electronic products to attract consumers' purchasing intentions. It is important to understand the consumer behavior towards electronic product that has the country of origin and brand image for contrasted from other products. This research is aimed to reveal: (1) the effect of country of origin on purchase intention of ASUS Smartphone in Semarang, (2) the effect of brand image on purchase intention of ASUS Smartphone in Semarang, and (3) the effect of country of origin and brand image on purchase intention of ASUS Smartphone in Semarang. This research type is explanatory research, with the techniques of data collection through the questionnaire. Sampling techniques using a purposive sampling technique. The sample in this research are 100 respondents which is a ASUS smartphone users in Semarang. This research using techniques of quantitative analysis. Quantitative analysis using the test validity, reliability test, coefficient of correlation, linear regression analysis, the determination coefficient, and significance test with SPSS 16.0. Based on the analyzed result, it can be concluded that there was a significant positive effect among country of origin, brand image, and perceived on purchase intention of ASUS smartphone in Semarang. However, to increase purchase intention, it is necessary to increase creativity and innovation in the products, as well as advances and developments in the latest technology.Keywords: Country of origin; Brand image; Purchase IntentionÂ Abstrak: Globalisasi dan kemajuan teknologi tengah menjadi pusat perhatian masyarakat lokal maupun internasional pemasar mengembangkan produk elektronik untuk menarik minat beli konsumen. Maka penting untuk memahami perilaku konsumen terhadap produk elektronik yang memiliki country of origin, brand image, dan persepsi untuk mebedakan dari produk lainnya. Penelitian ini bertujuan untuk mengetahui: (1) pengaruh country of origin terhadap minat beli smartphone ASUS di Kota Semarang, (2) pengaruh brand image terhadap minat beli smartphone ASUS di Kota Semarang, dan (3) pengaruh country of origin dan Â brand image terhadap minat beli smartphone ASUS di Kota Semarang. Tipe penelitian ini adalah explanatory research, dengan teknik pengumpulan data melalui kuesioner. Teknik pengambilan sampel menggunakan teknik non-purposive sampling. Sampel dalam penelitian ini berjumlah 100 responden yang merupakan pengguna smartphone ASUS di Kota Semarang. Penelitian ini menggunakan teknik analisis kuantitatif. Analisis kuantitatif menggunakan uji validitas, uji reliabilitas, koefisien korelasi, analisis regresi linier, koefisien determinasi dan uji signifikansi dengan bantuan SPSS 16.0. Berdasarkan hasil analisis dapat disimpulkan terdapat pengaruh yang positif dan signifikan antara country of origin dan brand image terhadap minat beli smartphone ASUS di Kota Semarang. Namun untuk meningkatkan minat beli perlu ditingkatkannya kreativitas dan inovasi pada produk-produk yang dihasilkan, serta kemajuan dan perkembangan pada teknologi terbaru.Kata kunci: Country of origin; Brand image; Minat Beli